Predicting Inequality of Opportunity and Poverty in India Using Machine Learning - Mehta, Balwant Singh; Srivastava, Ravi.; Dhote, Siddharth; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open-access book combines traditional economic methods with newer machine learning techniques such as regression trees and random forests to analyse data and provide an in-depth analysis of inequality of opportunity and poverty in India. Using data from national surveys and unique sources like night-time satellite images and location data of points of interest, it explores different aspects of inequality and poverty. The book adopts a unique interdisciplinary approach, blending theories and methods from sociology, economics, geography, anthropology, and computer science to explore three key aspects of human well-being: income, health, and education, focusing on regional disparities. It aims to offer practical insights for policymakers and researchers who want to address social and economic inequalities in India.
Introduction -- Concept and Measurement of IOp -- Decomposition of Inequality of Opportunity -- Predicting Poverty with Machine Learning and Geospatial Data -- Inequality of Opportunity in Education -- Inequality of Opportunity in Health Care Services -- Conclusion and Way Forward.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Development economics; Economic policy; Social policy; Labor economics; Development Economics; Socio-Economic Policy; Labor Economics